Mass spectrometry of extracellular vesicles. Issue 1 (20th February 2015) - Pocsfalvi, Gabriella; Stanly, Christopher; Vilasi, Annalisa; Fiume, Immacolata; Capasso, Giovambattista; Turiák, Lilla; Buzas, Edit I; Vékey, Károly
Abstract : The review briefly summaries main features of extracellular vesicles, a joint terminology for exosomes, microvesicles, and apoptotic vesicles. These vesicles are in the center of interest in biology and medical sciences, and form a very active field of research. Mass spectrometry (MS), with its specificity and sensitivity, has the potential to identify and characterize molecular composition of these vesicles; but as yet there are only a limited, but fast‐growing, number of publications that use MS workflows in this field. MS is the major tool to assess protein composition of extracellular vesicles: qualitative and quantitative proteomics approaches are both reviewed. Beside proteins, lipid and metabolite composition of vesicles might also be best assessed by MS techniques; however there are few applications as yet in this respect. The role of alternative analytical approaches, like gel‐based proteomics and antibody‐based immunoassays, are also mentioned. The objective of the review is to give an overview of this fast‐growing field to help orient MS‐based research on extracellular vesicles. © 2015 Wiley Periodicals, Inc. Mass Spec Rev 35: 3–21, 2016.